Spatial localisation of actin filaments across developmental stages of the malaria parasite. - Fiona Angrisano; David T Riglar; Angelika Sturm; Jennifer C Volz; Michael J Delves; Elizabeth S Zuccala; Lynne Turnbull; Chaitali Dekiwadia; Maya A Olshina; Danushka S Marapana; Wilson Wong; Vanessa Mollard; et al. (PLoS ONE, 2012)
Actin dynamics have been implicated in a variety of developmental processes during the malaria parasite lifecycle. Parasite motility, in particular, is thought to critically depend on an actomyosin motor located in the outer pellicle of the parasite cell. Efforts to understand the diverse roles actin plays have, however, been hampered by an inability to detect microfilaments under native conditions. To visualise the spatial dynamics of actin we generated a parasite-specific actin antibody that shows preferential recognition of filamentous actin and applied this tool to different lifecycle stages (merozoites, sporozoites and ookinetes) of the human and mouse malaria parasite species Plasmodium falciparum and P. berghei along with tachyzoites from the related apicomplexan parasite Toxoplasma gondii. Actin filament distribution was found associated with three core compartments: the nuclear periphery, pellicular membranes of motile or invasive parasite forms and in a ring-like distribution at the tight junction during merozoite invasion of erythrocytes in both human and mouse malaria parasites. Localisation at the nuclear periphery is consistent with an emerging role of actin in facilitating parasite gene regulation. During invasion, we show that the actin ring at the parasite-host cell tight junction is dependent on dynamic filament turnover. Super-resolution imaging places this ring posterior to, and not concentric with, the junction marker rhoptry neck protein 4. This implies motor force relies on the engagement of dynamic microfilaments at zones of traction, though not necessarily directly through receptor-ligand interactions at sites of adhesion during invasion. Combined, these observations extend current understanding of the diverse roles actin plays in malaria parasite development and apicomplexan cell motility, in particular refining understanding on the linkage of the internal parasite gliding motor with the extra-cellular milieu.